AB0593 INTERSTITIAL LUNG DISEASE ASSOCIATED WITH ANCA POSITIVITY: A RETROSPECTIVE ANALYSIS. (June 2019) - Juman, Sabrina; Oldroyd, Alexander; Chaudhuri, Nazia; Haque, Sahena
Abstract : Background: The association between interstitial lung disease (ILD), anti-neutrophil cytoplasmic autoantibodies (ANCA) and vasculitis has been described in case reports and small series. Treatment approaches have been diverse and include the use of various immunosuppressive agents. To date, little is known about the clinical phenotype and outcomes of ANCA associated ILD. Objectives: The objectives of this study were to ascertain the prevalence of ANCA in ILD patients at a tertiary respiratory centre; describe the clinical phenotype; describe lung function outcome and examine the progression of computed tomography (CT) patterns in patients with ANCA-associated ILD. Methods: This retrospective observational study was conducted at a tertiary ILD centre. Patients with ILD and coexistent ANCA were identified from review of a clinical database. All patients had a multidisciplinary team diagnosis of ILD confirmed on CT scan and had no other underlying cause of ILD identified. Data regarding clinical characteristics, CT scan pattern of ILD, pulmonary function tests (PFTs) and treatment were collected retrospectively. Results: Sixty-nine patients that fulfilled the criteria of coexistent ILD and ANCA were identified. Thirty-one patients were cANCA positive and 38 patients pANCA positive with a median age of 67 years (interquartile range 15 years). Sixteen patients were positive for MPO–ANCA and eight for PR3-ANCA. Only 26% of the cANCA and 24% of the pANCA population had coexistent ANCA-associated vasculitis diagnosed by a MDT clinic comprising of rheumatology, respiratory and renal physicians. Figures 1 and 2 show the treatment distribution in c and pANCA populations respectively. Approximately 23% of the entire study population did not require treatment. Of the patients that required treatment, steroids were used in 81% of cANCA and 61% of pANCA patients. The most commonly used disease modifying anti-rheumatic drug was mycophenolate mofetil followed by azathioprine and/or methotrexate. Only a small proportion of patients required cyclophosphamide or rituximab. At 24-months follow-up, 68% were alive, 22% deceased and data unavailable for 10% of the cANCA group compared to 61% alive, 2% end-of-life, 16% deceased and 21% unavailable data in the pANCA group. Diffusing capacity of the lungs for carbon monoxide (DLCO) declined in both p and cANCA groups over the first 12 months before improving. This improvement in PFTs is likely due to treatment escalation over time. Overall the pANCA group showed a mixture of progressive fibrotic and inflammatory CT features while the cANCA and MPO-ANCA groups showed predominantly progressive fibrotic CT findings. Kruskal-Wallis test was used to determine whether there was an association between the PFTs of the p and cANCA population at three to six months, 12 months and 24 months. This test was then repeated for comparison of the MPO-ANCA and PR3-ANCA study population. There was no significant difference in lung function over time between the pANCA and cANCA group or MPO-ANCA and PR3-ANCA group. Conclusion: Although pANCA is thought to be associated with ILD or pulmonary fibrosis, we detected equal numbers of c and pANCA in a well characterised population of ILD patients. Approximately one quarter of patients with p or cANCA had an MDT diagnosis of ANCA-associated vasculitis. The clinical and CT characteristics did not differ between c and pANCA ILD patients. The two-year mortality of patients with ANCA and ILD was significant (22% in cANCA-ILD and 16% in pANCA). In surviving patients, the FVC and DLCO improved over a 24-month period. Disclosure of Interests: None declared